Performing Sustainability in West Africa: Cultural Practices and Policies for Sustainable Development - Meike Lettau; Christopher Yusufu Mtaku; Eric Debrah Otchere (Routledge, 2023)
This book discusses the role of cultural practices and policy for sustainable development in West Africa across different artistic disciplines, including performance, video, theatre, community arts and cultural heritage. Based on ethnographic field research in local communities, the book presents findings on current debates of cultural sustainability in Nigeria, Ghana, Cameroon and Benin. It provides a unique perspective connecting cultural studies, conflict studies and practical peacebuilding approaches through the arts. The first part pays particular attention to aspects of social cohesion and the circumstances of internally displaced persons e. g. caused by the Boko Haram insurgency in Northeast Nigeria. The second part focuses on cultural policy issues and challenges in the context of sustainable development, investigating participatory approaches and bottom-up processes, the role of governments and civil society, as well as performing arts organizations and universities in policy making and implementation processes. Performing Sustainability in West Africa presents research results and new methods on the role of artistic and cultural practices in conflict situations as well as current debates in cultural policy for researchers, academics, NGOs and students in cultural studies, sustainable development studies and African studies.
Keywords: 300; Development economics and emerging economies